2015
DOI: 10.4172/2155-9597.1000252
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Protein Energy Malnutrition Deficiency among Children Under Five Years at Alruhal Camp-Kass Locality South Darfur State 2012 Sudan

Abstract: This cross-sectional descriptive study to measure the risk factors of protein energy malnutrition deficiency, this study designed to cover (n=384 child), the study Shows that most affected children were those whose families income per month was less than 250 SDG, (18.5%), The prevalence of malnutrition increase among children there is mothers illiterate (13.4%), the study found that the male more affected (12.5%) than female (8.5%) and children there age (6-12 month most affected 7.7%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
3
4
0
Order By: Relevance
“…Regarding the prevalence of malnutrition among boys children, the findings of this study is similar to study findings of the study conducted among under five year's children at Al-Ruhal Internal Displaced Population Camp at Kass locality in South Darfur State, 2011; i.e. The malnutrition was higher in males (12.5%) than females (8.5%) [19]. this may due to the male children in rural are more active, so they need more energy.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the prevalence of malnutrition among boys children, the findings of this study is similar to study findings of the study conducted among under five year's children at Al-Ruhal Internal Displaced Population Camp at Kass locality in South Darfur State, 2011; i.e. The malnutrition was higher in males (12.5%) than females (8.5%) [19]. this may due to the male children in rural are more active, so they need more energy.…”
Section: Discussionsupporting
confidence: 87%
“…The cluster mean of 3.55 shows that ignorance on food nutrition, non-practice of exclusive breastfeeding and poor weaning methods were the major factors that predispose children to protein energy malnutrition. This findings agrees with [11] whose study showed that PEM was more common among children from the lower social class (69.4%) and those predominantly breast fed for three months or less (48.6%) compared to exclusively breast fed children (18.9%). The reason for this may not be unconnected to the fact that poor families have low purchasing power for adequate nutritious foods for their families.…”
Section: Predisposing Factors To Protein Energy Malnutrition In Umuarsupporting
confidence: 82%
“…Also holds that mothers abandon breastfeeding because they do not know how to get their baby position properly or to suffer pain and discomfort during breastfeeding. The above finding also agrees with the finding of [11] which showed that poor weaning of children is one of the predisposing factors to protein energy malnutrition. The implication of this finding is that enhancement in both knowledge and practice is greatly required on the following areas of exclusive breast milk, initiation of breast milk, continuous feeding of breast milk and good dietary practices.…”
Section: Predisposing Factors To Protein Energy Malnutrition In Umuarsupporting
confidence: 82%
See 1 more Smart Citation
“…The low rate of exclusive breast feeding noted in this review despite the Baby Friendly Initiatives is also very worrisome. Poverty and illiteracy as risk factors for PEM [9]. A management and prevention of malnutrition are based on the following strategies and adequate general ration for the whole community.…”
Section: Associated Risk Factors For Pemmentioning
confidence: 99%